Compound Heterozygous Sickle and Thalassemia Trait: A Case Report - Shrestha, Bikash; Karmacharya, Kavita; Singh, Jasjit; Kotwal, Jyoti; Devgan, Amit (Journal of Nepal Paediatric Society, 2011)
Sickle cell disease is a type of hemoglobinopathy, which is fairly common in certain parts of the world. We would like to report an interesting case of a child who was labeled as sickle cell anemia but subsequently turned out to be a case of compound heterozygous sickle cell and thalassemia trait. Keywords: Sickle cell disease; haemoglobinopathy; thalassemia; hydroxyurea; globin; electrophoresis; HPLC DOI: 10.3126/jnps.v31i2.4414 J Nep Paedtr Soc 2010;31(2):130-133